Pemberdayaan Masyarakat Melalui Program Coporate Sosial Responsilibility Di Desa Kawasi Kecematan Obi Kabupaten Halmahera Selatan Provinsi Maluku Utara - Siar, Fergo . (JURNAL ILMIAH SOCIETY, 2015)
villagers with PT Gane Permai Sentosa Company.The aim of research to describe and analyze the implementation of community empowerment through its Corporate Social Responsibility PT GanePermai Sentosa company Kawasivillage Obi districts of South Halmahera regency North Molucca province. This study used qualitative methods.Â The data can be used that interview and documentation of observations.This study aims to describe and analyze the community development through Corporate Social Responsibility ProgramPTGane Permai Sentosa.Â Research result in Kawasi village of Obi district South Halmahera. The company has not acted upon that community empowerment is Fisherman's Village of Kawasi, Garden Road 1500 Meter, Making concrete fence, Drenase Making, Making Harbour Bridge.Â While community empowerment that has been undertaken by the company, but has not fulfilled properly, namely: Farmers, Building 93 Housing, Giving scholarships to children who went on Bachelors Degrees and Masters, Building worship places of Muslims (Mosque) and Christian worship places (Church) and Junior High School. Keywords: Community, Empowerment, Corporate Social Responsibility.